On the Error Probability of Cognitive RF-FSO Relay Networks Over Rayleigh/EW Fading Channels With Primary-Secondary Interference - Eylem Erdogan; Nihat Kabaoglu; Ibrahim Altunbas; Halim Yanikomeroglu (IEEE Photonics Journal)
Free space optical (FSO) communication has emerged to provide line of sight connectivity and higher throughput over unlicensed optical spectrums. Cognitive radio (CR), on the other hand, can utilize the radio frequency (RF) spectrum and allow a secondary user (SU) to share the same spectrum with the primary user (PU) as long as the SU does not impose interference on the PU. Owing to the potential of these emerging technologies, to provide full spectrum efficiency, this paper focuses on the mixed CR RF-FSO transmission scheme, where RF communication is employed at one hop followed by the FSO transmission on the other hop in a dual-hop decode-and-forward (DF) configuration. To quantify the performance of the proposed scheme, closed form error probability is derived over Rayleigh/Exponentiated Weibull (EW) fading distributions by considering the statistical and instantaneous feedback channel of the primary network. We also employed an asymptotic analysis to illustrate the diversity gain of the overall system. We believe that the proposed scheme can be applicable to the 5G+ networks where an unlicensed university student connects to the home computer with the aid of an FSO path.